Novel terpilih Shahnon Ahmad : satu kajian pendekatan gender - Ooi, Eng Lye (Dewan Bahasa dan Pustaka, 2005)
Gender relations among the Malay in novels written by Shahnon Ahmad, a Malaysian writer; literary criticism.